2019
DOI: 10.1186/s12968-019-0531-x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation is associated with reduced myocardial fibrosis. A cardiovascular magnetic resonance study with native T1 mapping

Abstract: Background The measurement of native T1 through cardiovascular magnetic resonance (CMR) is a noninvasive method of assessing myocardial fibrosis without gadolinium contrast. No studies so far have evaluated native T1 after renal transplantation. The primary aim of the current study is to assess changes in the myocardium native T1 6 months after renal transplantation. Methods We prospectively evaluated 44 renal transplant patients with 3 T CMR exams: baseline at the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…The use of newer T1 mapping techniques without gadolinium (native T1) has demonstrated increased myocardial T1 relaxation times indicative of diffuse interstitial fibrosis in ESRD [13,14] and early-stage CKD [12]. Although KT was associated with reduced septal native T1 [15], probably related to reduction in diffuse interstitial fibrosis, in this study we failed to prove associations between improvements in LV GLS with reductions in native T1. It has been suggested that changes in myocardial systolic and diastolic deformation are functional markers of diffuse interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The use of newer T1 mapping techniques without gadolinium (native T1) has demonstrated increased myocardial T1 relaxation times indicative of diffuse interstitial fibrosis in ESRD [13,14] and early-stage CKD [12]. Although KT was associated with reduced septal native T1 [15], probably related to reduction in diffuse interstitial fibrosis, in this study we failed to prove associations between improvements in LV GLS with reductions in native T1. It has been suggested that changes in myocardial systolic and diastolic deformation are functional markers of diffuse interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 64%
“…Previous CMR studies have shown subclinical features of myocardial disease characterized by reduced left ventricular (LV) GLS and increased myocardial fibrosis, as assessed by T1 mapping, in CKD [ 12 ] and ESRD [ 13 , 14 ]. Although KT was associated with reduced myocardial fibrosis [ 15 ], previous FT-CMR [ 16 ] and speckle-tracking echocardiography (STE) [ 17 , 18 ] studies found different results about the effects of KT in LV GLS, which is the most reliable and studied strain parameter. Nevertheless, the relationships between LV GLS, cardiac structure and myocardial tissue characteristics in this setting are unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 106 Native T1 measurements, a method of assessment of myocardial fibrosis in CMRI without gadolinium contrast, was explored by Contti et al where it was found that 6 months following renal transplantation, the native myocardial T1 time decreased, suggestive of regression of reactive fibrosis. 107 These findings demonstrate significant reverse cardiac remodelling as a result of renal transplantation in this high-risk population group.…”
Section: Managementmentioning
confidence: 69%
“…The use of newer T1 mapping techniques without gadolinium (native T1) has demonstrated increased myocardial T1 relaxation times indicative of diffuse interstitial brosis in ESRD [13,14] and early-stage CKD [12]. Although KT was associated with reduced septal native T1 [15], probably related to reduction in diffuse interstitial brosis, in this study we failed to prove associations between improvements in LV GLS with reductions in native T1. It has been suggested that changes in myocardial systolic and diastolic deformation are functional markers of diffuse interstitial brosis.…”
Section: Discussionmentioning
confidence: 67%
“…Previous CMR studies have shown subclinical features of myocardial disease characterized by reduced left ventricular (LV) GLS and increased myocardial brosis, as assessed by T1 mapping, in CKD [12] and ESRD [13,14]. Although KT was associated with reduced myocardial brosis [15], previous FT-CMR [16] and speckle-tracking echocardiography (STE) [17,18] studies found different results about the effects of KT in LV GLS, which is the most reliable and studied strain parameter. Nevertheless, the relationships between LV GLS, cardiac structure and myocardial tissue characteristics in this setting are unknown.…”
Section: Introductionmentioning
confidence: 99%